2022
DOI: 10.1037/lhb0000510
|View full text |Cite
|
Sign up to set email alerts
|

A call to dismantle systemic racism in criminal legal systems.

Abstract: Objectives: In October 2021, the American Psychological Association (APA) passed a resolution addressing ways psychologists could work to dismantle systemic racism in criminal legal systems. In the present report, developed to inform APA’s policy resolution, we detail the scope of the problem and offer recommendations for policy makers and psychologists to address the issue by advancing related science and practice. Specifically, we acknowledge the roots of modern-day racial and ethnic disparities in rates of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 195 publications
0
12
0
Order By: Relevance
“…We recommend that legal systems prioritize education and professional training programs designed to enhance awareness regarding racism and ways to reduce racial inequity broadly within legal systems (Worden et al, 2020) and for such training to be high-quality, continual, and supported by holistic, positive institutional norms and engagement (Eberhardt, 2020). In line with recommendations from a recent American Psychological Association resolution on dismantling systemic racism in the legal system (Najdowski & Stevenson, 2022), we also encourage efforts to ensure diversity among criminal justice professionals. Indeed, criminal justice professionals of color might be more sensitive than White professionals to the role of racism within the justice systems (Thompson et al, 2016) and less racially discriminatory in their treatment of people of color (Ba et al, 2021; Swencionis et al, 2021).…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…We recommend that legal systems prioritize education and professional training programs designed to enhance awareness regarding racism and ways to reduce racial inequity broadly within legal systems (Worden et al, 2020) and for such training to be high-quality, continual, and supported by holistic, positive institutional norms and engagement (Eberhardt, 2020). In line with recommendations from a recent American Psychological Association resolution on dismantling systemic racism in the legal system (Najdowski & Stevenson, 2022), we also encourage efforts to ensure diversity among criminal justice professionals. Indeed, criminal justice professionals of color might be more sensitive than White professionals to the role of racism within the justice systems (Thompson et al, 2016) and less racially discriminatory in their treatment of people of color (Ba et al, 2021; Swencionis et al, 2021).…”
Section: Discussionmentioning
confidence: 73%
“…We also encourage policy and practice changes designed to eliminate racial bias in child sexual abuse case decision-making, which might include masking child race during caseworker decision-making (Cosgrove, 2021) to ensure that race does not influence case outcomes. Yet, research is needed to explore the potential for benefit and harm of race masking within legal decision-making (Najdowski & Stevenson, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As expected, Black students were more likely than their White counterparts to agree they experience stereotype threat in their encounters with police. Although those results suggested that Black and White people have psychologically distinct experiences of police encounters, considering they are in reality policed in qualitatively different ways (Hinton & Cook, 2021; Najdowski & Stevenson, 2022), an alternative explanation is that the Black and White students in our first study imagined different kinds of encounters that posed different levels of risk for being perceived or treated as a criminal. We accounted for this possibility in a second study by asking Black and White men to imagine how they would feel in the same hypothetical police encounter (Najdowski et al, 2015).…”
Section: Stereotype Threat and The Psychological Experience Of Police...mentioning
confidence: 76%
“…Future research may also be able to disentangle the multiple levels of identity that may operate to modify the lawyer identity. Past studies have drawn conclusions that the criminal and civil justice system and the institution of law give preference to white men and continue to reify systemic racism through their processes and interactions (Alexander 2010; Najdowski and Stevenson 2022). Future work can work to illuminate this by investigating the intersectional nature of the woman lawyer identity and start to disentangle experiences of people from a variety of backgrounds, including people of color, those from low-income backgrounds, and other minoritized groups.…”
Section: Discussionmentioning
confidence: 99%